2012
DOI: 10.1501/ashd_0000000080
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing in Turkish hospitals: a systematic review

Abstract: Dış kaynak kullanımı devlet hastanelerinde temel bir strateji haline gelmekte ve son zamanlarda tanınırlığı artmaktadır. Türkiye'de bu trendi oluşturan itici güç, özel sektördeki baskıların ve rekabetin kamu sektörünü daha verimli kılacağı gerçeğine dayanarak Sağlık Bakanlığı tarafından başlatılmıştır. Bu çalışmanın amacı, sistematik analiz yoluyla Türkiye'deki hastanelerde dış kaynak kullanımı konusunda elde edilen farklı araştırma bulgularını karşılaştırmak, bütünleştirmek ve gelecekteki araştırmalara yöneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Outsourcing is the mechanism of assigning some of the central or non-operational activities of the organization to its supplier outside the organization ( 6 ). There are many reasons to outsource services, including reducing costs, increasing efficiency, focusing on core processes, improving skills, reducing service delivery time and increasing competitive advantage ( 6 - 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Outsourcing is the mechanism of assigning some of the central or non-operational activities of the organization to its supplier outside the organization ( 6 ). There are many reasons to outsource services, including reducing costs, increasing efficiency, focusing on core processes, improving skills, reducing service delivery time and increasing competitive advantage ( 6 - 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Downsizing was identified as one of the main factors in political dimension. This intervention can improve the performance of public hospitals by reducing bureaucratic costs, service delivery duration, increasing efficiency and enhancing skills [34]. In addition, as this study indicated, healthcare technological advances can be assessed and used appropriately to decrease the burden on healthcare system and enhance the efficiency of services.…”
Section: mentioning
confidence: 92%
“…In fact, outsourcing is a purchasing mechanism in which an organization purchases a special service at an agreed quality and quantity for a determined period from a service provider which is out of the organization [3,4] and controlled via a contract or collaborative management [5]. Outsourcing could merge private sector advantages-such as efficiency [1,6] and consumer satisfaction [7,8]-into the public sector and avoid its disadvantages-such as inattention to equity and social responsibility [9]. This could result in generating internal market or quasi-market in the public sector that promotes competition [10,11].…”
Section: Introductionmentioning
confidence: 99%